The impact of human–animal interactions during micro-breaks on sleep quality and work engagement: A within-person approach - Junça Silva, A. (Applied Psychology: An International Review, 2025)
This study draws on the Recovery Step Model and the Conservation of Resources (COR) theory to propose a framework that examines how and when sleep quality influences work engagement. Specifically, we tested a moderated mediation model where sleep quality predicts employees' work engagement through enhanced self-regulatory resources at the within-person level. Additionally, we investigated whether human–animal interactions (HAIs), during micro-breaks, moderate this indirect relationship. Overall, 155 teleworkers participated in a 10-day diary study (155*10 = 1550 measurement occasions). The multilevel analysis revealed that daily sleep quality positively predicted employees' work engagement by enhancing their self-regulatory resources. Moreover, this relationship was stronger for individuals who engaged in micro-breaks involving interactions with their companion animals. As the frequency of HAIs during micro-breaks increased, so did employees' levels of work engagement. These findings expand the recovery step model and the furr-recovery method by demonstrating that HAIs serve as beneficial micro-breaks during work hours, providing a restorative function that enhances work engagement. In sum, at least one HAI during the workday could have significant implications for employees' work engagement.